2020
DOI: 10.3121/cmr.2020.1546
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Perioperative Bridging Anticoagulation in Patients with Atrial Fibrillation Undergoing Elective Surgical Procedures: A Meta-analysis

Abstract: The study objective was to determine if peri-operative bridging anticoagulation in patients with atrial fibrillation is beneficial or harmful.Design: Systematic review and meta-analysis.Setting: Inpatient or in-hospital setting.Participants: Adults with atrial fibrillation having a CHADS2 score >1 undergoing elective surgical procedure on anticoagulation.Methods: A systemic search of multiple databases (Cochrane, Medline, PubMed) was performed regarding studies conducted on efficacy and safety of perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…The present study confirms the overall increase of bleeding complications during bridging that has been described in several meta-analyses [ 5 , 21 ]. Although our incidence of bleeding complications declined after implementation of the risk-adjusted regimen, it remained above our previous reported incidence in patients without OAC (10.3% in period 2 vs. 6.1% control group of period 1 [ 8 ]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confirms the overall increase of bleeding complications during bridging that has been described in several meta-analyses [ 5 , 21 ]. Although our incidence of bleeding complications declined after implementation of the risk-adjusted regimen, it remained above our previous reported incidence in patients without OAC (10.3% in period 2 vs. 6.1% control group of period 1 [ 8 ]).…”
Section: Discussionsupporting
confidence: 92%
“…The general necessity of perioperative bridging has been challenged by two randomized controlled trials demonstrating no benefit concerning the incidence of thromboembolism from LMWH bridging in patients on warfarin OAC [ 16 , 18 ]. However, there is yet no consensus whether high risk patients might still profit from LMWH bridging and individual management is still recommended [ 5 , 21 , 23 ]. A single study on bridging in abdominal malignancy surgery reported no increase of bleeding complications or thromboembolism by heparin bridging [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest systematic review on this topic by Siddiqui et al in 2021 considered studies published up to January 2019, and hence does not incorporate the findings of the PERIOP 2 trial published in 2021. 16 As part of our updated systematic review, we will not only incorporate the data from these studies, but also undertake subgroup analysis on patients with high CHA2DS2-VASc scores (ie, 2 or more), as well as those anticoagulated with DOACs, both of which represent gaps in literature that are yet to be answered. Lastly, we will assign a level of certainty to the results of each outcome via the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) 17 approach to allow for easy translation into clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary search of PROSPERO, MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis was conducted, and no in-progress systematic reviews on the topic were identified. The latest systematic review on this topic by Siddiqui et al in 2021 considered studies published up to January 2019, and hence does not incorporate the findings of the PERIOP 2 trial published in 2021 16 . As part of our updated systematic review, we will not only incorporate the data from these studies, but also undertake subgroup analysis on patients with high CHA2DS2-VASc scores (ie, 2 or more), as well as those anticoagulated with DOACs, both of which represent gaps in literature that are yet to be answered.…”
Section: Introductionmentioning
confidence: 99%